PENGARUH PERSEPSI SISWA TENTANG VARIASI MENGAJAR GURU DAN CARA BELAJAR SISWA TERHADAP HASIL BELAJAR IPS TERPADU - AMBAR WIDYA LESTARI; YON RIZAL; NURDIN NURDIN (JEE (Jurnal Edukasi Ekobis), 2013)
On learning activities in school is confronted by the problem of result and studen achievment. Student learning outcomes are influenced by many factors, both internal and external factors. One of external factors that can determine the variety of teachers outcomes are pursuing teacher while one internal factor is how student learn. The purpose of this study was to obtain data on the effect of variations in students perceptions of teachers teaching and students learning of SMP N 7 Bandarlampung academic year 2012/2013. The population in this study were students of grade VIII first semester SMP N 7  Bandarlampung with 180 students for five classes. By using the Slovin formula in probability sampling with a sample obtained 124 peoples, and then performed proportional allocation sampling with samples that taken to be more proportional. The method that used in this study is verification with ex post facto approach. The problem and research is the perception of teachers to teach students about the negative variation and the ineffectiveness of student learning are thought to affect learning outcomes of IPS Integrated for student grade VIII SMP N 7 Bandarlampung for first semester on academic year 2012/2013. Based on the analysis of the results for this study shown that : (1). There is a positive and significant effect of variations in student’s perception about teachers teaching outcomes of IPS Integrated for student grade VIII SMP N 7 Bandarlampung for first semester on academic year 2012/2013. (2). There is a positive and significant of how student learn outcomes IPS integrated for student grade VIII SMP N 7 Bandarlampung for first semester on academic year 2012/2013. (3). There is a positive and significant the effect of variations in students perceptions of teachers teaching and how student learn outcomes of IPS Integrated for student grade VIII SMP N 7 Bandarlampung for first semester on academic year 2012/2013. Keywords  :    Variations in students perceptions about teachers teaching and how student learn